2017
DOI: 10.3847/2041-8213/aa920c
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational Waves and Gamma-Rays from a Binary Neutron Star Merger: GW170817 and GRB 170817A

Abstract: On 2017 August 17, the gravitational-wave event GW170817 was observed by the Advanced LIGO and Virgo detectors, and the gamma-ray burst (GRB) GRB170817A was observed independently by the Fermi Gamma-ray Burst Monitor, and the Anti-Coincidence Shield for the Spectrometer for the International Gamma-Ray Astrophysics Laboratory. The probability of the near-simultaneous temporal and spatial observation of GRB170817A and GW170817 occurring by chance is 5.0 10 8 -. We therefore confirm binary neutron star mergers … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

61
2,079
4
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 3,078 publications
(2,221 citation statements)
references
References 337 publications
61
2,079
4
9
Order By: Relevance
“…This multimessenger data provided convincing answers to many outstanding questions. For instance, the detection of a short gamma ray burst (GRB) 1.7 seconds after GW170817 [24][25][26], and subsequent kilonova [27][28][29][30][31][36][37][38][39][40][41][42][43][44], confirmed that BNS mergers are a progenitor of these events. Lanthanide signatures in the kilonova light curves also showed BNS mergers to be a major site for nucleosynthesis of elements heavier than iron [40,44,47,48].…”
Section: Introductionmentioning
confidence: 78%
“…This multimessenger data provided convincing answers to many outstanding questions. For instance, the detection of a short gamma ray burst (GRB) 1.7 seconds after GW170817 [24][25][26], and subsequent kilonova [27][28][29][30][31][36][37][38][39][40][41][42][43][44], confirmed that BNS mergers are a progenitor of these events. Lanthanide signatures in the kilonova light curves also showed BNS mergers to be a major site for nucleosynthesis of elements heavier than iron [40,44,47,48].…”
Section: Introductionmentioning
confidence: 78%
“…Finally, let us mention that Einstein-aether theory is highly constrained by various experimental observations, especially the speed bound derived from GW170817 and GRB 170817A [5,[43][44][45]. Apart from this speed bound and the absence of the gravitational Cherenkov radiation, there are constraints from the observations of pulsars (such as the post-Newtonian parameters, |α 1 | < 4 × 10 −5 [65] and |α 2 | < 2 × 10 −9 [66,67] …”
Section: Einstein-aether Theorymentioning
confidence: 99%
“…[33] also discussed the constraints that the generalized TeVeS theory should satisfy. Similarly to Einstein-aether theory, it is also constrained by the solar system test (i.e., the constraints on α 1 and α 2 2 ), the absence of the gravitational Cherenkov radiation, and the recent GW speed bound [45], etc. Taking all the constraints into account, it was found that the speed of the one 2 The expressions for α 1 and α 2 in generalized TeVeS theory are even more complicated, so they are not presented here, either.…”
Section: Generalized Teves Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…So when a magnetic jet system is newly established in a new direction [58] during a merger event, the jet flow has to be re-established (the characteristic velocity for this may be the relativistic speed of sound c/ √ 3), particles have be newly injected, and built up as a viable population. The observation of a time lag between the GW event and the HE photons [59] of 1.74 s is compatible with this characteristic distance for a central black hole of a mass of order 1 to 2 Solar masses: the characteristic distance introduced above yields a range of expected time lags of 10 −0.45 to 10 +1.05 s for a neutron star merger resulting in a black hole, fully compatible with the observations; the additional time lags due to the build-up of a viable population of energetic particles may be as fast or even faster. This time scales with the mass of the central black hole, and so the merger of two super-massive black holes of order 10 8 Solar masses the corresponding time scale is then about 3 years.…”
Section: High-energy Neutrino Emission In Agnmentioning
confidence: 99%